2023
DOI: 10.3389/fpls.2023.1108515
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich water treatment increased several phytohormones and prolonged the shelf life in postharvest okras

Abstract: Hydrogen-rich water (HRW) treatment has been reported to delay the softening and senescence of postharvest okras, but its regulatory mechanism remains unclear. In this paper, we investigated the effects of HRW treatment on the metabolism of several phytohormones in postharvest okras, which act as regulatory molecules in fruit ripening and senescence processes. The results showed that HRW treatment delayed okra senescence and maintained fruit quality during storage. The treatment upregulated all of the melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It has been reported that the treatment with exogenous melatonin induced the expression of melatonin biosynthetic genes, thus increasing the levels of endogenous melatonin in postharvest horticultural products ( Cao et al., 2016 ; Hu et al., 2017 ). Our recent study also found the hydrogen rich water delayed senescence in okras after harvest via upregulating the expression of melatonin synthesis-related genes and endogenous melatonin content ( Dong et al., 2023 ). Therefore, the data presented here clearly showed that suspension of senescence in okras treated with melatonin could be due to the upregulation of melatonin biosynthetic genes and the resultant increase in endogenous melatonin content.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…It has been reported that the treatment with exogenous melatonin induced the expression of melatonin biosynthetic genes, thus increasing the levels of endogenous melatonin in postharvest horticultural products ( Cao et al., 2016 ; Hu et al., 2017 ). Our recent study also found the hydrogen rich water delayed senescence in okras after harvest via upregulating the expression of melatonin synthesis-related genes and endogenous melatonin content ( Dong et al., 2023 ). Therefore, the data presented here clearly showed that suspension of senescence in okras treated with melatonin could be due to the upregulation of melatonin biosynthetic genes and the resultant increase in endogenous melatonin content.…”
Section: Discussionmentioning
confidence: 89%
“…The visual evaluation of senescence index on the surface of ten okras from each replicate was conducted. Senescence was rated according to methods described by Dong et al. (2023) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that agriculture techniques should use hydrogen as a treatment for plants [11]. According to the study, hydrogen-rich water enhanced many phytohormones and extended the shelf life of postharvest okras, showing that it has the potential to improve fruit quality [12]. One study found that hydrogen plays a role in enhancing the activity of antioxidant enzymes and the transcription of related genes, which can promote the growth of mung bean and rice seedlings and roots [13].…”
Section: Introductionmentioning
confidence: 99%